The Authority national and international criminal judiciary (Al-Mansour Journal, 2022)
This research deduced from the subject that national court authority must beviewing in to acts against natural persons or moral's that they make crimesdescribed in to interfacing authority with some excepting.Otherwise the international courts joining with authority wider more thannational authority without missing the national authority unless thecircumstances that cannot ability to Judge the persons who their crimes arecalled internationality.So under all these thinks this research will be divided in to three parts chapterone will be defined all content as competences theory as generally, the secondchapter explain the competences of courts national and (International), under all Two criminals acts will be determined and finally chapter three is to explain if there is a conflict between the two courts or more suitable. Under all these in above this research is to investigating and insuring that there is deeply infraction in the basis system of decisions to security council authority Idle, stopping the investigating or juridical for personal not shortly with under as renewing and discussed to a abolish all the paragraph (B) fromthe article number (13) in the system .